2011
DOI: 10.1590/s1807-59322011000900016
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal tobacco exposure is related to neurobehavioral modifications in infants of adolescent mothers

Abstract: INTRODUCTION:Prenatal tobacco exposure interferes with neonatal outcomes.OBJECTIVE:To determine the neonatal neurobehavioral effects of in utero tobacco exposure.METHODS:This prospective cross-sectional study included healthy, term, with birth weight appropriate for gestacional age neonates without exposure to alcohol, drugs, or infections, born to adolescent mothers without psychiatric disorders or post-traumatic stress. Infants were classified according to in utero tobacco exposure, as identified by the Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Although a growing body of literature exists on MCSDP-associated alterations in placental methylation, there is much work yet to be done to elucidate the specific signaling pathways and mechanisms involved in mediating the relationship between MCSDP and disease risk in later life. Ongoing cohort studies may help to further discern the risks posed by MCSDP to infant and child health outcomes, including risks for respiratory disorders, 110 , 111 , 113 , 114 , 116 adverse neurodevelopmental outcomes, 15 , 16 , 60 , 61 , 64 , 85 , 145 and obesity, 17 19 all of which have been linked to MCSDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a growing body of literature exists on MCSDP-associated alterations in placental methylation, there is much work yet to be done to elucidate the specific signaling pathways and mechanisms involved in mediating the relationship between MCSDP and disease risk in later life. Ongoing cohort studies may help to further discern the risks posed by MCSDP to infant and child health outcomes, including risks for respiratory disorders, 110 , 111 , 113 , 114 , 116 adverse neurodevelopmental outcomes, 15 , 16 , 60 , 61 , 64 , 85 , 145 and obesity, 17 19 all of which have been linked to MCSDP.…”
Section: Discussionmentioning
confidence: 99%
“… 58 By negatively impacting the function of these placental cell types, MCSDP can increase the risk of placenta previa, placental abruption, 59 and other reproductive problems. MCSDP is associated with detriments to infant neurobehavior 15 , 16 , 60 64 and the development of autoimmune diseases. 65 67 Both active 68 73 and passive 71 , 73 75 MCSDP are linked to small-for-gestational-age infants.…”
Section: Cigarette Smoking In Pregnancy: Known Risks To Fetal Health mentioning
confidence: 99%
“…4 , in a cross-sectional observational study involving 388 infants born to teenage mothers, observed that newborns of mothers who smoked (6.5%) showed, within the first 24-48 hours of life, significant difference in the number of waking periods and excitability, when compared to those born to nonsmoker mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, Fried y Smith (2001) encontraron variaciones en el desempeño en tareas con demandas de control cognitivo de adolescentes de 13 a 16 años de edad, que habían sido expuestos al consumo de ambas sustancias durante la etapa prenatal. Recientemente, Barros, Mitsuhiro, Chalem, Laranjeira, & Guinsburg (2011) encontraron que la exposición a tabaco durante el embarazo se asoció con niveles más altos de excitabilidad y de dificultades de regulación emocional en la etapa perinatal. Si bien aún es necesario incluir en este tipo de estudios análisis que permitan identificar los mecanismos de mediación a través de los cuales estos agentes generan su impacto, los resultados sugieren que la exposición prenatal a tabaco y marihuana se asocia con el desarrollo de dificultades en el procesamiento autorregulatorio durante las primeras dos décadas de vida.…”
Section: Exposición a Tóxicos Ambientales Y A Drogas Legales E Ilegalesunclassified